Development of polymer-bound fast-dissolving metformin buccal film with disintegrants - Haque SE (Dove Medical Press, 2015)
Shaikh Ershadul Haque, Angappan Sheela Materials Chemistry Division, Centre for Nanomaterials, School of Advanced Sciences, VIT University, Vellore, India Abstract: Fast-dissolving drug-delivery systems are considered advantageous over the existing conventional oral dosage forms like tablets, capsules, and syrups for being patient friendly. Buccal films are one such system responsible for systemic drug delivery at the desired site of action by avoiding hepatic first-pass metabolism. Metformin hydrochloride (Met), an antidiabetic drug, has poor bioavailability due to its high solubility and low permeability. The purpose of the study reported here was to develop a polymer-bound fast-dissolving buccal film of metformin to exploit these unique properties. In the study, metformin fast-dissolving films were prepared by the solvent-casting method using chitosan, a bioadhesive polymer. Further, starch, sodium starch glycolate, and microcrystalline cellulose were the disintegrants added to different ratios, forming various formulations (F1 to F7). The buccal films were evaluated for various parameters like weight variation, thickness, folding endurance, surface pH, content uniformity, tensile strength, and percentage of elongation. The films were also subjected to in vitro dissolution study, and the disintegration time was found to be less than 30 minutes for all formulations, which was attributed to the effect of disintegrants. Formulation F6 showed 92.2% drug release within 6 minutes due to the combined effect of sodium starch glycolate and microcrystalline cellulose. Keywords: chitosan, sodium starch glycolate, microcrystalline cellulose, drug-delivery system, immediate release